2022
DOI: 10.1007/s41999-022-00641-5
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of sarcopenia and the frailty phenotype in the outpatient care of older people: implementation and typical values obtained from the Newcastle SarcScreen project

Abstract: Purpose Sarcopenia and the frailty phenotype both indicate older adults at risk of adverse health outcomes and yet are not widely assessed in practice. We developed the Newcastle SarcScreen to enable assessment of these two ageing syndromes during clinical care. In the setting of our Older People’s Medicine Day Unit, our aims were to describe the implementation of the SarcScreen and to examine the typical values obtained. Methods The SarcScreen comprised h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
(33 reference statements)
3
8
0
Order By: Relevance
“…When assessed by low hand grip strength alone, probable sarcopenia was present in over half of participants ( n = 61, 19/31) and almost all by poor chair rise test performance (90%, n = 28/31). In a relatively similar cohort to our study group, Dodds et al [ 21 ] found similar patterns, with 84% of patients meeting the criteria for probable sarcopenia based on low hand grip strength, and 66% were frail based on Fried phenotype [ 21 ]. The latter was a large study of older adults attending an acute day unit in the UK ( n = 552) with a mean age of 80.1 ± 7.7 years.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…When assessed by low hand grip strength alone, probable sarcopenia was present in over half of participants ( n = 61, 19/31) and almost all by poor chair rise test performance (90%, n = 28/31). In a relatively similar cohort to our study group, Dodds et al [ 21 ] found similar patterns, with 84% of patients meeting the criteria for probable sarcopenia based on low hand grip strength, and 66% were frail based on Fried phenotype [ 21 ]. The latter was a large study of older adults attending an acute day unit in the UK ( n = 552) with a mean age of 80.1 ± 7.7 years.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, low physical activity was prevalent, with participants reporting an estimated 11 daytime hours spent sitting. While these chronic conditions and patterns of sedentary behaviour have been reported in older people in acute settings and in longitudinal datasets [ 20 , 21 , 42 , 43 ], few studies have focused on older populations supported by formal home care [ 24 ]. The findings suggest opportunities for appropriate physical activity and dietary intervention to address sarcopenia, frailty, and malnutrition in this group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,49 More directly, clinical practice has an important role to play in screening and identifying those who have sarcopenia, or are at greatest risk of developing sarcopenia, so these individuals can be prioritised for intervention. 50…”
Section: Future Directionsmentioning
confidence: 99%